PENERAPAN MODEL PEMBELAJARAN RCCDE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGAN - Wulandari, Anita; Roudlotul Hikamah, Siti; Nurjanah, Umi (JURNAL BIOSHELL, 2021)
Learning model is a whole series of teaching material presentation which includes all aspects before and after learning. The problem in this study is that student learning outcomes are still lo and lacking enthusiasm in the learning process, where the value of student learning outcomes is still much below the KKM. This type of research uses PTK, with a quantitative data collection in the from of student learning outcomes tests and qualitative data obtained from intervies and studend documentation data. With 23 students as research subjects. Based on the results of this study, the average cognitive score of srtudentd in cycle I was 73. In the first cycle the average cognitive score of students II was 82, so there was an increase of 9%. So the application of the RCCDE learning model can improve students learning outcomes in the material of interaction of living things with the environment so that it can help in the student learning proses.Keywords: RCCDE model, learning outcomes, the interaction of living things with the environment